Application of neuro-fuzzy system for predicting the success of a company in public procurement - Pamučar, Dragan; Bozanic, Darko; Puška, Adis; Marinković, Dragan (Decision Making: Applications in Management and Engineering, 2022)
The paper presents a neuro-fuzzy system for evaluating and predicting the success of a construction company in public tenders. This model enables companies to operate sustainably by assessing their own position in the market. The model was based on data from a seven-year study, where data from the first six years were used to adjust the model, while data from the last year of the study were used for testing and validation. The neuro-fuzzy model was tuned using the Artificial Bee Colony algorithm.